Research note: Legal implications of soundalike hotels in China: Haiyatt and Marvelot - Karen Edwards, J.; Rosenbaum, M.; Cheng, Mingming (Pergamon, 2018)
This article introduces the concept of the soundalike hotel to the hospitality and tourism disciplines. More specifically, this article explores the legal implications surrounding the Haiyatt and Marvelot hotel brands in China, which sound like the Hyatt and Marriott brands, respectively. Soundalike hotels would be perceived by courts around the world as trademark infringement. However, China's legal system accepts the existence of soundalike hotels and overlooks the illegality of their existence. This article clarifies, from a legal perspective, why soundalike hotels are accepted in China and offers insights into how hotel organizations may lessen their chances of experiencing trademark infringement in China. The article uses TripAdvisor data to show that most Haiyatt and Marvelot guests do not realize that these hotels are engaging in deceptive practices by using soundalike brands. Thus, neither Hyatt nor Marriott have legal precedence to show that guests are confused by the existence of soundalike hotels.